Long-term Complications of COVID-19 in Nursing Staff; a Retrospective Longitudinal Study - Etemad, Koorosh; Hatami, Hossein; Nikpeyma, Mahnaz; Mowla, Forough; Fallah Atatalab, Fatemeh (Archives of Academic Emergency Medicine, 2023)
Introduction: Although the lungs are the main target of coronavirus disease (COVID-19), infection is also associated with a high rate of extra-pulmonary complications. This study aimed to evaluate the one-year incidence of long-term COVID-19 complications among the nursing staff. Methods: This study is a retrospective longitudinal study. All nursing staff working in public hospitals affiliated with Shahid Beheshti University of Medical Sciences who had been affected with COVID-19 were included in the study via convenience sampling method. The patients were recruited from 20th February 2020 to 20th March 2021. Result: 1762 nursing staff with a mean age of 35.08 ± 8.02 (Range: 22-66) years were studied (73.5% female). The results showed that among those who reported at least one type of complication, the duration of complications was significantly longer than 1 week and the median was 8 weeks. The findings demonstrated that complications occurred in 65% of infected females. For men, this rate was 62.3%. Generalized pain, anxiety disorders, and skin complications were among the complications that were significantly more common in women than in men. Additionally, the incidence of anosmia, ageusia, anxiety disorders, and skin complications was significantly higher in younger people than in older people. The comparison of complications revealed that nurses were significantly more likely than other occupations to experience respiratory complications, anosmia and ageusia, generalized pain, and skin complications and that outpatients experienced significantly more complications than hospitalized patients. Conclusion: The one-year cumulative incidence of long-term complications in nursing staff with COVID-19 was 64.3%. The most common complications were respiratory complications, generalized pain, anosmia, and ageusia, respectively.